Rencana Strategi Implementasi Laodato Si di Universitas Katolik Darma Cendika - Albertus Daru Dewantoro; Zakaria Halim (Industrial & System Engineering Journals (ISEJOU), 2023)
The implementation of Laudato Si' as a commitment to environmental protection and sustainable practices should thrive within the environment of Darma Cendika Catholic University (UKDC). This engagement needs to be systematically organized, starting with a strategic plan. The research aims to formulate recommendations for the implementation strategy of engaging with Laudato Si', considering the available resources and external factors that influence the UKDC environment. The research was conducted using SWOT analysis and QSPM method. The results of the research, through SWOT analysis, recommend eight alternative strategies. Furthermore, through QSPM analysis, these strategies were ranked based on the consideration of weights and Attractive Scores of each Critical Success Factor (CSF). The strategy with the highest total score is considered a priority. The analysis results indicate that the alternative strategy for implementing MBKM Independent Project by students and lecturers has the highest Total Attractive Score (TAS) of 2.79. The second-ranked alternative strategy is the development of a micro-scale PLTS prototype with a TAS value of 2.73.